The Influence of Hedonic Shopping Motivation and Fashion Involvement to Impulse Buying in E-Commerce - SEPTIANI, Widya; KUNTARDINA, Ari; ADIPUTRA, Eka; HIDAYATIN, Dina Alafi; HIDAYAH, Nur (Journal of Tourism Economics and Policy, 2024)
Research to understand influence of HSM and FI on IB in e-commerce. Quantitative research with stratified random sampling technique. Data was collected through questionnaires given to 82 students who used e-commerce, with multiple linear regression data analysis. The results show HSM does not affect IB in e-commerce. While FI has a significant effect on IB in e-commerce. HSM and FI simultaneously have a significant effect on IB in e-commerce. E-commerce merchants are expected to continue to adapt to trends, changes in consumer behavior and follow technological developments in an effort to maintain consumer satisfaction. They need to identify consumer needs and preferences, and implement innovative solutions to enhance the shopping experience.